Occupational Injuries Among Construction Workers by Age and Related Economic Loss: Findings From Ohio Workers' Compensation, USA: 2007-2017 - Harpriya Kaur; Steven J. Wurzelbacher; P. Tim Bushnell; Stephen Bertke; Alysha R. Meyers; James W. Grosch; Steven J. Naber; Michael Lampl (Elsevier, 2023)
Background: This study examined age-group differences in the rate, severity, and cost of injuries among construction workers to support evidence-based worker safety and health interventions in the construction industry. Methods: Ohio workers' compensation claims for construction workers were used to estimate claim rates and costs by age group. We analyzed claims data auto-coded into five event/exposure categories: transportation incidents; slips, trips, and falls (STFs); exposure to harmful substances and environments; contact with objects and equipment (COB); overexertion and bodily reaction. American Community Survey data were used to determine the percentage of workers in each age group. Results: From 2007-2017, among 72,416 accepted injury claims for ∼166,000 construction full-time equivalent (FTE) per year, nearly half were caused by COB, followed by STFs (20%) and overexertion (20%). Claim rates related to COB and exposure to harmful substances and environments were highest among those 18-24 years old, with claim rates of 313.5 and 25.9 per 10,000 FTE, respectively. STFs increased with age, with the highest claim rates for those 55-64 years old (94.2 claims per 10,000 FTE). Overexertion claim rates increased and then declined with age, with the highest claim rate for those 35-44 years old (87.3 per 10,000 FTE). While younger workers had higher injury rates, older workers had higher proportions of lost-time claims and higher costs per claim. The total cost per FTE was highest for those 45-54 years old ($1,122 per FTE). Conclusion: The variation in rates of injury types by age suggests that age-specific prevention strategies may be useful.